Muslim women activist`s approach to reforming Islamic family law: the problem of contextualization in Malaysia - Haneef, Sayed Sikandar Shah (2015)
The rise of Muslim feminist movement is a positive development in the intellectual landscape of Muslim debate on women`s rights in contemporary Muslim societies. As a pressure group, their struggle to improve the condition of women against the odds of conservative Muslim legal scholars‟ resistance and culture of patriarchy indubitably has somewhat impacted reforms in the domain of state- enacted Islamic family laws, such as in Malaysia. Nevertheless, beyond the polemics over the legitimacy of their approach, their main handicap is finding grounds for acceptability in society. To bridge this gap, the paper argues for a productive mediating dialogue between Muslim feminist and mainstream outlooks for socially acceptable reform.